Wages in Eastern Germany still considered more unjust than in the west - Stefan Liebig; Sebastian Hülle; Jürgen Schupp (DIW Economic Bulletin, 2014)
Almost twenty-five years after the fall of the Berlin Wall, far more eastern Germans are unhappy with their income than western Germans. In 2013, around 44 percent of employed eastern Germans rated their earnings as unjust compared with approximately one-third in western Germany. Although the east-west gap has been diminishing since 2005-to around 12 percent in 2013-this is not because eastern Germans feel that they are now being paid more fairly, but rather because the perceived injustice in western Germany increases. One of the reasons why a relatively high level of perceived wage inequality persists in eastern Germany is the fact that there are still differences between East and West in incomes within occupations. Evidence of this is seen in analyses conducted by the Socio-Economic Panel (SOEP).
Keywords: I31; Z10; 330; German Unification; Justice; Wages; SOEP